Impacto da pandemia da covid-19 no ensino e uso do diamino fluoreto de prata e razões de falhas de pulpectomias: da mínima a máxima intervenção em dentes decíduos - Sityá, Débora Santos (2022)
This thesis is composed of two scientific articles whose main themes are the impact of COVID-19 on the teaching and use of silver diamine fluoride (SDF) and reasons for pulpectomy failures in primary teeth. Article 1: The impact of COVID-19 pandemic on silver diamine fluoride use in Pediatric Dentistry in Brazilian dental schools: a cross-sectional questionnaire-based survey. The aim of this study was to evaluate the impact of the COVID-19 pandemic on the teaching and use of SDF in Pediatric Dentistry in country graduation courses. An online questionnaire, including six questions on teaching and using the SDF before, during and after the pandemic, was sent to 265 courses. The 65 answers were analyzed descriptively and using the chi-square test. Even with the onset of the COVID-19 pandemic, SDF is not a theoretical class topic in 13.8% of dental schools and 23.1% of dental schools have not included SDF in clinical practice. The COVID-19 pandemic has not impacted the teaching and use of SDF in Brazilian dental schools. Article 2: Reasons for failure in primary molars’ pulpectomies: A systematic review. This study systematically reviewed clinical studies evaluating pulpectomies in primary molars with at least 1 year of followup, aiming to identify the reasons for failure. Of the 2.784 potentially eligible studies in PubMed, Scopus, ISI Web of Science, Scielo and Cochrane Library electronic databases, 34 met the inclusion criteria. The failure rate of pulpectomies ranged from 0% to 46%. Failures of pulpectomies were evaluated clinically and/or radiographically in almost all studies, however, incomplete or unclear information was found on the reasons for failures.